Recent Advance in Intelligent Vehicle (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The aim of this reprint is to immerse the reader in the latest technologies in autonomous vehicles, including environment perception technologies, planning and control technologies and so on. In this reprint, leading experts in the field share their state-of-the-art works, insights, and visions for the future. Together, we embark on a journey to unlock the full potential of the intelligence in autonomous vehicles, seeking sustainable solutions that improve the safety, comfort, intelligent performance.